Male Rat Susceptibility for Liver and Kidney Injury - Hamad, Sarkawt; Othman, Karwan I.; Hamad, Karwan J.; Rasul, Balkes H.; Abdulla, Shorsh M.; Ismael, Ismael A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2016)
The experimental study of this paper was designed to investigate male rat susceptibility to liver injury. A combination of two experimental animal models (Lead acetate for tissue injury (80 mg / L) and castration) had been used on twenty male rats, they were divided into two groups sham (n = 10); castrated (n = 10). Results revealed that, liver weight reduced significantly (P < 0.05) in sham group in comparison with castrated rats, but kidney weight changed slightly. Also, serum aminotransferase (AST) was significantly higher in sham versus castrated rats. Neither alanine aminotransferase (ALT) and alkaline phosphatase (ALP) nor malondialdehyde (MDA) changed. In conclusion, the absence of male sex hormone would delay tissue injury of male rat organs especially liver organ.